Answer:5 min I think
Step-by-step explanation: 5 min I think
You should know that:
(a+b)(a+b)(a+b)
=a(a+b)(a+b)+b(a+b)(a+b)
=a(a²+2ab+b²)+b(a²+2ab+b²)
=a³+2a²b+ab²+a²b+2ab²+b³
=a³+3a²b+3ab²+b³
-----------------
If a=5x and b=-4y
(5x+(-4y))³
=(5x-4y)³
=(5x)³+3(5x)²(-4y)+3(5x)(-4y)²+(-4y)³
=125x³+3(25x²)(-4y)+15x(16y²)-64y³
=125x³+75x²(-4y)+240xy²-64y³
=125x³-300x²y+240xy²-64y³
<em><u>Answer 1: 177 – 77 = 100 </u></em>
<em><u>Answer 2: (7+7) * (7 + (1/7)) = 100</u></em>
- Multiply (-2x-4) by -5:
[(-5)(-2x) + (-5)(-4)] +5x - 4 = -29
= 10x+20+5x-4=-29
- Combine Like Terms:
(10x+5x) + (20-4) = -29
15x+16=-29
- Subtract 16 from each side
15x+16 -16 = -29 -16
15x = -45
x = -3